Phylogeny and Phylogeography of Aethalops from Sundaland using Mitochondrial 12S rRNA Gene - Tingga,, R. C. T.; Abdullah, M.T (2012)
One of the smallest fruit bats in Pteropodidae is Aethalops. This genus is known to be confined in montane forest, which is generally above 1000 meters above sea level (m.a.s.l.). Bornean Aethalops is generally known as Aethalops alecto in most previous literature. This study aimed at constructing the phylogenetic relationship of A. alecto and A. aequalis in Sundaland and determining gene flow within Bornean A. aequalis using partial mitochondrial 12S rRNA gene. Seven populations of A. aequalis, representing Sabah and Sarawak and a single population from Kalimantan were observed, whereas A. alecto were represented by four populations from Indonesian islands. From the phylogenetic analyses and minimum spanning network, there were two major clusters within the genus, with Aethalops. A. aequalis in Borneo were clearly distinguished from A. alecto from the islands of Indonesia. However, phylogenetic analyses within A. aequalis were unresolved at the population levels in Sabah and Sarawak. Therefore, it can be concluded that A. aequalis is the species found only in Borneo. High genetic similarities were detected among the populations of A. aequalis in Sabah and Sarawak. Hypothetically, the Kalimantan harbors ancestral populations of A. aequalis in Borneo, with high genetic divergence from Sabah and Sarawak populations.